STRIP MALL APPLYING A PARAMETRIC DESIGN IN THE DISTRICT OF LOS OLIVOS, METROPOLITAN LIMA, PERÚ - Trujillo-Quispe, Rafael (2023)
The objective of this article is to present the virtues offered by a project strategy based on the use of new technologies. In an architectural project that meets architectural and social needs, in metropolitan Lima, Perú. The parametric design allowed the new generations of Peruvian architects to explore new possibilities when thinking about the form, space, and order of architecture. They will be able to learn about and develop the potential of using software and how it facilitates not only the creation of the "form" of the building but also the construction and execution of the project since this type of architecture is mistakenly believed to be difficult to execute and requires of a new and expensive construction system. The proposed architectural object is influenced by the context and acquires characteristics of the environment, with the aim that the user's perception associates the architecture with the environment that surrounds it.